Hydrogels as promising platforms for engineered living bacteria-mediated therapeutic systems - Shuangjiang Yu; Hongcheng Sun; Yongguang Li; Shu Wei; Jiayun Xu; Junqiu Liu (Materials Today Bio, 2022)
The idea of using engineered bacteria as prospective living therapeutic agents for the treatment of different diseases has been raised. Nevertheless, the development of safe and effective treatment strategies remains essential to the success of living bacteria-mediated therapy. Hydrogels have presented great promise for the delivery of living bacterial therapeutics due to their tunable physicochemical properties, good bioactivities, and excellent protection of labile payloads. In this review, we summarize the hydrogel design strategies for living bacteria-mediated therapy and review the recent advances in hydrogel-based living bacterial agent delivery for the treatment of typical diseases, including those for digestive health, skin fungal infections, wound healing, vaccines, and cancer, and discuss the current challenges and future perspectives of these strategies in the field. It is believed that the importance of hydrogel-based living bacteria-mediated therapy is expected to further increase with the development of both synthetic biology and biomaterials science in the future.